(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article examines how different languages influence through, “Alice’s adventures in the wonderland “by Lewis Caroll. This work also translated into diverse range of languages such as Uzbek, Russian, English and so on. When it comes to the novel,it goes into facing variations in two languages ,particularly Uzbek and English languages.In one word we can see a lot of distinctions in this work during analayzing through uzbek and english languages. Alice’s adventures in Wonderland translated as “Alisaning mo’jizalar o’lkasidagi sarguzashtlari” by M .Zohidova in the mutolaa app .Additionally ,the novel has been trnslated into 175 languages, with Japanese having the most editions.